ANALISIS PENGGUNAAN MEDIA SOSIAL SMARTPHONE OLEH SISWA DALAM PROSES PEMBELAJARAN SOSIOLOGI KELAS XI IIS 1 SMAN 01 TOHO - Murni, Julia Sari; Bahari, Yohanes; Rustiyarso, Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The title of this thesis is ?Analysis of Smartphone Social Media Usage in Sociology Learning Process by Eleventh grade Students of Social Sciences of Senior High School of SMAN 1 Toho?. The problem of this study is how eleventh grade students of Social Sciences of Senior High School of SMAN 1 Toho utilize Smartphone Social Media in Sociology Learning Process, Based on this problem, the sub-issue of this study is formulated, specifically: How is the activity of utilizing Smartphone Social Media in terms of innovative, creative and effective learning? This study applied descriptive method with qualitative approach. Observation, interview and documentation are tools used for collecting data. The findings indicate that (1) characterized as an innovative learning. Teachers manage to create a new innovation in the learning process, particularly the use of social media smartphone and this innovation activity has not been employed by other teachers in that school. (2) characterized as an creative learning, Teachers have succeeded in utilizing smartphones as a media to access the sources of information that can support the learning process. (3) characterized as an effective learning. Instead of the benefits of smartphone social media usage in sociology learning process, the findings also reveal that sociology learning process facilitated by smartphones is ineffectivesince several students have on smartphones. Keywords: Sociology learning, smartphone social media